Airborne forward‐looking radar imaging approach via modified propagator method in planar phased array - Yin, Lannuo; Wang, Yong (IET radar, sonar & navigation, 2024)
Forward‐looking radar imaging is a top priority due to a variety of applications. An airborne forward‐looking radar imaging approach via a modified propagator method (MPM) based on the planar phased array is proposed. It can obtain a better focusing effect without range migration correction. Through the MPM algorithm, the azimuth resolution can be enhanced greatly. Compared with the conventional synthetic aperture radar imaging algorithm, the left‐right ambiguity process can be avoided by generating two‐dimensional spatial spectra. Furthermore, the imaging results of different numbers of elements are given to provide an assessment of the imaging performance. Additionally, the authors proposed to apply the scanning planar phased array configuration to airborne forward‐looking two‐dimensional imaging for the first time. The validity of the method is proven by experiments. The image is more focused. Furthermore, the results of the experiments verify that the proposed method is fit for high‐speed situation and aircraft height variation condition. An airborne forward‐looking radar imaging approach via the modified propagator method (MPM) based on the planar phased array is proposed. It can image the forward‐looking scene accurately even in high‐speed situation without range migration correction.